Global longitudinal strain in hypertensive patients with low exercise capacity (Texas Journal of Medical Science, 2022)
Arterial hypertension is associated with a high rate of morbidity and death because to its negative effects on a variety of systems, particularly the cardiovascular system. There will be growing myocardial fibrosis before cardiac function insults of a hypertension patient become apparent. Diastolic impairment is a prominent component of this illness, and despite the growing recognition of its importance, it is still underappreciated due to its challenging diagnosis and lack of effective therapies. The study's goal was to assess global longitudinal strain in hypertensive individuals with inadequate exercise ability. After receiving their verbal and written consent, a total of 40 young people participated in this study. The research took place from January through April of 2021. Sample is collected from consultation room in Furat teaching hospital. A sample was taken from the Furat teaching hospital's consulting room. They were separated into two groups based on their ECG treadmill test results: those with fair or normal functional capacity >7 MET (n=25) and those with reduced functional capacity ≤7 MET (n=25). No important difference in the average GLS in these two groups is observed (P value:0.6). Conclusion: In hypertension individuals with inadequate functional capability, global longitudinal strain does not vary